A cloud-based system for distance learning supported by Fog-Cloud cooperation. (24th December 2021) - Larcher, Lucas; Ströele, Victor; Dantas, Mário
The cloud computing paradigm fosters a distance learning modality where students do not need to be physically present on the course place, and the teaching and learning process occurs by Virtual Learning Environments (VLE). A centralised information unit (a university) supports outside units with the necessary equipment and knowledge. In this ordinary structure, the cloud paradigm is mighty and primarily used, but it has some limits. The challenge is to turn it scalable, considering that the users' infrastructure is characterised by poor internet connectivity. A Fog-Cloud model can be conceived to tackle this problem using a local pre-processing data stage before sending them to the cloud. This paper presents a situation in Brazilian universities and proposes a low-cost solution using a Fog-Cloud computing paradigm to support a VLE. In the evaluation process, an experiment using real data was carried out, and the results obtained successfully point to the proposal's viability.